Chromosomal aberration frequencies determined by conventional methods: Parallel increases over time in the region of a petrochemical industry and throughout the Czech Republic - Šrám, Radim J; Rössner, Pavel; Beskid, Olena; Bavorová, Hana; Očadlíková, Danuše; Solanský, Ivo; Albertini, Richard J (Chemico-biological interactions, 2007)
The rationale for cytogenetic monitoring to determine if safe maximum allowable concentrations (MAC) of genotoxic chemicals are being maintained in a workplace is that exposure levels that do not increase chromosomal aberration frequencies are without harmful effects. Such monitoring, widely used in occupational health programs in the Czech Republic (CR), includes workers exposed to 1,3-butadiene (BD) or other chemicals. Studies of BD exposed workers in the years 1992, 1993, 1994, 1998, and 2004 compared mean frequencies of cells carrying chromosomal aberrations (frequency of aberrant cells=%AB.C.) in exposed workers with those in non-exposed matched controls in the same plant or in other individuals living in the region of the same petrochemical industry. Workers potentially exposed to acrylonitrile at this site were also evaluated in 2000, along with another unexposed matched control group. The %AB.C. values of exposed workers and their controls were also compared with reference values determined for normal individuals (ages 20-59 years) throughout the CR. Substantial discrepancies were noted between subjects in the region of the petrochemical industry (exposed workers and controls) for the years 2000 and 2004 and the reference CR-wide normal values that had been determined during an earlier time period. The matched non-exposed controls at the petrochemical industry site showed a mean %AB.C. value of 1.56+/-1.23% (N=25) in 1998; this rose to a mean of 2.65+/-2.29% (N=33) in 2000. In 2004, values for non-exposed matched controls at the industry site were 2.64+/-1.75% for males (N=25) and 2.38+/-1.74% (N=26) for females. However, the earlier determined CR-wide %AB.C. mean reference values for normal individuals were 1.77+/-1.16% (N=1305) for the interval 1977-1988 and 1.45+/-1.17% (N=2140) for the interval 1991-1999. As both reference values are substantially lower than those determined in 2000 and 2004 for the non-exposed matched controls at the petrochemical industry site, an analysis of the CR-wide mean normal individual reference values for this same 2000-2004 period was conducted. Unexpectedly, it was found that this reference value too had risen to 1.95+/-1.36% (N=1045) and was comparable to the concurrent matched control values at the petrochemical industry site where the monitoring studies were conducted. This substantial increase in %AB.C. values in 2000 and 2004, therefore, has occurred throughout the CR and is probably unrelated to chemicals uniquely present at the petrochemical industry site.
Keywords: financování organizované; dospělí; genetické techniky; akrylonitril; Female; maximální přípustná koncentrace; lymfocyty; Adult; ženské pohlaví; Acrylonitrile; Time Factors; časové faktory; Maximum Allowable Concentration; lidé; chemický průmysl; Butadienes; Chemical Industry; Financing, Organized; Male; chromozomální aberace; Czech Republic; Genetic Techniques; butadieny; Česká republika; Lymphocytes; lidé středního věku; mužské pohlaví; Middle Aged; Chromosome Aberrations; Humans